Entre la escuela y el trabajo. El tránsito a la vida adulta de los jóvenes en la Ciudad de Buenos Aires y el Distrito Federal - Ferraris, Sabrina A.; Martínez Salgado, Mario (El Colegio de México A.C., 2015)
The transition to adulthood is a process that includes several experiences involving a balance between taking on and abandoning various roles. The life course perspective permits the study of subjects and their families over time and assumes transitions as diverse, socially created and shaped by historical circumstances and cultural traditions. This research analyzes the period between the end of school and the start of the working lives of young people from City of Buenos Aires in Argentina and the Federal District in Mexico at the start of this century.